Clinical Values of serum carcinoembryonic antigen (CEA), glycoprotein antigen (CA) 50, CA19-9, and CA72-4, and the soluble fragment of cytokeratin 19 (CYFRA21-1) in early screening and prognosis prediction of colon cancer: Clinical values of serum tumor markers - Zhang, Yingqiang; Song, Ze; Tang, Jun; Wu, Min; Li, Zhi (Journal of Medical Biochemistry, 2025)
aim: To investigate the clinical values of serum tumor markers carcinoembryonic antigen (CEA), glycoprotein antigen (CA) 50, CA19-9, and CA72-4, and the soluble fragment of cytokeratin 19 (CYFRA21-1) in early screening and prognosis prediction of colon cancer. Methods: 50 patients with colon cancer were enrolled into case group and 50 healthy people undergoing physical examination were enrolled into control group. The expressions of CEA, CA50, CA19-9, CA72-4, and CYFRA21-1 in two groups were compared.  Results: It was demonstrated that the expressions of CEA, CA50, CA19-9, CA72-4, and CYFRA21-1 among patients in case group were all superior to those among patients in control group (P
Keywords: Serum tumor markers; Colon cancer; Early screening; Prognosis; Recurrence and metastasis